2013
DOI: 10.1093/jac/dkt075
|View full text |Cite
|
Sign up to set email alerts
|

The cdr1B efflux transporter is associated with non-cyp51a-mediated itraconazole resistance in Aspergillus fumigatus 

Abstract: Objectives: Recent increases in triazole resistance in Aspergillus fumigatus have been attributed primarily to target site (cyp51A) mutations. A recent survey of resistant isolates in Manchester showed that .50% of resistant isolates had no mutation in cyp51A or its promoter. We investigated the mechanisms of resistance in clinical azole-resistant isolates without cyp51A mutations.Methods: Twelve azole-resistant isolates, 10 of which were itraconazole resistant, were studied. Bioinformatic comparisons between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
272
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(282 citation statements)
references
References 46 publications
9
272
0
1
Order By: Relevance
“…In this study, we have extended our understanding of this ABC transporter protein with the finding that Cdr1B/AbcB is critical for azole resistance in several common laboratory strains, detecting the polypeptide chain for the first time, localizing the protein to the plasma membrane, and providing evidence that this protein may be required in pathogenesis. Combined with the previous study (21), these data implicate Cdr1B/AbcB as an important participant in the biology of drug resistance in A. fumigatus.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In this study, we have extended our understanding of this ABC transporter protein with the finding that Cdr1B/AbcB is critical for azole resistance in several common laboratory strains, detecting the polypeptide chain for the first time, localizing the protein to the plasma membrane, and providing evidence that this protein may be required in pathogenesis. Combined with the previous study (21), these data implicate Cdr1B/AbcB as an important participant in the biology of drug resistance in A. fumigatus.…”
Section: Discussionsupporting
confidence: 77%
“…More recent surveys of azole-resistant clinical isolates found that a large fraction of these organisms contained no detectable change at their cyp51A locus (1,20). Importantly, overexpression of a gene encoding a Pdr5 homologue was found to be required for azole resistance in a strain with a normal cyp51A gene (21). Together, these findings support the view that, as in other fungal pathogens, transcriptional upregulation of ABC transporter gene expression is an important contributor to this clinically key phenotype.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Whereas the impact of specific transporters on azole resistance of A. fumigatus remains largely enigmatic, ABC transporter genes are up-regulated in response to azole exposure (AfuMDR1, AfuMDR2, and five genes designated abcA-E) (Tobin et al 1997;da Silva Ferreira et al 2006), and in resistant clinical isolates (Slaven et al 2002;Nascimento et al 2003). AfuMDR1, renamed CDR1B, encodes the only transporter implicated directly in A. fumigatus azole resistance (Fraczek et al 2013).…”
Section: Drug Effluxmentioning
confidence: 99%
“…The high-level pan-azole-resistant phenotype, particularly the high posaconazole MIC, suggests that these isolates have accumulated additional non-cyp51A resistance mechanisms. These could include the recently described overexpression of cyp51A, cyp51B, and the cdr1B efflux pump; for these three mechanisms, MICs of Ն8 mg/liter for itraconazole, 1 to 8 mg/liter for voriconazole, and 0.125 to 2 mg/ liter for posaconazole have been measured (9)(10)(11). Based on these reported phenotypes, particularly the low-level posaconazole resistance, these mechanisms are unlikely responsible for the highlevel pan-azole-resistant phenotype observed in these four patients' isolates.…”
mentioning
confidence: 99%